Palmitic Acid Induced a Long-Lasting Lipotoxic Insult in Human Retinal Pigment Epithelial Cells, which Is Partially Counteracted by TRAIL - Domenico Sergi; Enrico Zauli; Fabio Casciano; Paola Secchiero; Giorgio Zauli; Matteo Fields; Elisabetta Melloni (MDPI AG, 2022)
Hyperglycaemia and increased circulating saturated fatty acids are key metabolic features of type 2 diabetes mellitus (T2DM) that contribute to diabetic retinopathy pathogenesis. Contrarily, tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) has been shown to improve or prevent T2DM. This study aimed at investigating the effect of TRAIL in an in vitro model of human retinal pigment epithelium: the ARPE-19 cell line, treated with palmitic acid (PA) in the presence of high glucose concentration. PA caused a drop in cellular metabolic activity and cell viability as well as an increase in apoptosis rates, which were paralleled by an upregulation of reactive oxygen species (ROS) generation as well as mitochondrial fragmentation. Despite ARPE-19 cells expressing TRAIL-R2 at the cell surface, TRAIL failed to counteract the cytotoxic effects of PA. However, when TRAIL was used alongside PA and then removed or used alone following PA challenge, it partially attenuated PA-induced lipotoxicity. This effect of TRAIL appeared to rely upon the modulation of inflammation and ROS production. Thus, TRAIL exerted a trophic effect on ARPE-19 cells, which became evident only when the lipotoxic insult was removed. Nevertheless, whether recombinant TRAIL might have a therapeutic potential for the treatment of diabetic retinopathy requires further investigation.